Arranjos produtivos de cerâmica estrutural: uma análise comparativa dos arranjos localizados em Monte Camaelo (MG), Porangatu (GO) e Itabaianinlia (SE) - Ferreira, Juliene Barbosa (2017)
The Neoschumpeterian works recover the concept of innovation initially proposed by Schumpeter and extend it, involving the approach of National Innovation System (SNI) and Local Innovation Systems (SLI), which corresponds to a set of economic actors that manage to generate, modify and Technological innovations. At the heart of this approach is the discussion of collective efficiency, cooperation, and interaction between actors who, combined with the external economies, give companies in productive clusters a basis for increasing competitiveness through the generation of innovation. The question that guides the work is: how can cooperative relations assist in the process of learning and innovation in the local red ceramic arrangements located in Monte Carmelo, Porangatu and Itabaianinha? The main objective of this work is to make a comparative analysis of the cooperative relations and the innovations of the ceramist companies integrated to the local productive arrangements located in Monte Carmelo (MG), Porangatu (GO) and Itabaianinha (SE). The hypothesis adopted in this work is that the APL, whose companies present the highest degree of horizontal, vertical and institutional cooperation, has greater potential for innovation, greater collective efficiency and, therefore, better conditions for future development. In order to reach the proposed objective, we made use of the neoschumpeterian theoretical contribution linked to the APL concept to support the field research carried out and the results found. This work is characterized by being a case study. Data collection was performed from September 2015 to January 2016, using as a tool the questionnaire prepared by Redesist, widely tested for this purpose. The hypothesis adopted in this study was corroborated. It can be said that Monte Carmelo APL presented the highest degree of horizontal cooperation (among companies), vertical (with suppliers of inputs and services - marketing and accounting) and institutional (ACEMC, LEMC and FUCAMP). These cooperative relationships can be clearly observed in the promotion of actions to adapt to environmental regulations (joint actions for the recovery of degraded areas, for reforestation and for the regularization of clay extraction) and for the promotion of quality certification (ISO 9001). Arrangement companies. There was a partnership between the association, the laboratory and the companies, to solve these relevant issues. It was also diagnosed that it was the arrangement that promoted a greater number of innovative activities that included the largest number of companies in the arrangement. It was also verified that the APL of Monte Carmelo has been adopted as reference by the other two APLs, having been visited by the businessmen of the APL of Porangatu and cited in the interview with the executive director of SEDETEC (SE), as an example of APL To be followed. Therefore, the greater degree of cooperation allowed greater potential for innovation and with this greater collective efficiency.